P182 Is it useful to perform a full physical examination in asymptomatic patients with late syphilis?. (23rd May 2012) - Dabis, R; Radcliffe, K
Abstract : Background: In late and congenital syphilis a thorough physical examination should be undertaken for signs of syphilis as per British Association for Sexual Health and HIV guidelines. This should include examination of skin and mucosal surfaces, lymph nodes, the cardiovascular and neurological systems. Aims: To audit all cases of late syphilis at our centre to see if a full cardiovascular and neurological examination was documented and also to see if a full examination contributed to the management of asymptomatic patients. Methods: A total of 648 notes were identified as late syphilis from KC60 codes from our local database. Records were from the period 1994 to 2010.The following information was extracted from the clinical records: age, ethnicity, gender, sexuality, symptomatic/asymptomatic, cardiovascular and neurological examination findings and further action taken where applicable. 148 notes were unavailable. 20 notes were excluded. Therefore 480 notes in total were audited. Results: Of the 480 patients, 262 (55%) were of Black Caribbean ethnicity, 75 (16%) White British, 68 (14%) Black African and 75 (16%) others. 240 (50%) were heterosexual males, 206 (43%) heterosexual females, 31 (6%) men who have sex with men. Information on sexual orientation was not available in 3 (1%). 295 patients were asymptomatic of which 288 (98%) had normal physical examinations. Seven asymptomatic patients had positive clinical findings but these did not lead to a diagnosis of cardiovascular or neurological syphilis. In 99 cases a full examination was not documented and in 21 cases patients declined or defaulted further follow-up. There were 65 symptomatic patients all had abnormal physical findings. Conclusion: In view of the absence of significant clinical examination findings in asymptomatic patients with late syphilis we believe that a physical examination is not a necessary element in the management of such cases and should be omitted.